2014
DOI: 10.1016/j.canlet.2014.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E3 metabolism and cancer

Abstract: The anticancer activity of n-3 fatty acids, especially those derived from fish, such as eicosapentaenoic acid (EPA) and docosahexaenoic acid) (DHA), has been studied for centuries. While there is a growing body of evidence that EPA and DHA may influence cancer initiation and development through targeting multiple events of tumor development, the underlying mechanisms responsible for these activities are still not fully understood. A number of studies have suggested that the anticancer activities of EPA and DHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 115 publications
1
45
0
3
Order By: Relevance
“…While less relevant to the current model, EPA is metabolized by COX-2 to form PGE 3 , which has anti-prolfierative effects in cancer (38). The small amounts of PGE 3 found in the colon are likely due to EPA metabolism via COX-2.…”
Section: Discussionmentioning
confidence: 99%
“…While less relevant to the current model, EPA is metabolized by COX-2 to form PGE 3 , which has anti-prolfierative effects in cancer (38). The small amounts of PGE 3 found in the colon are likely due to EPA metabolism via COX-2.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with ARA, EPA is a poor substrate for COX enzymes 48, 49 . Previous studies have shown that PGE 3 has less detrimental or even beneficial effects on cancer, the biology of PGE 3 was discussed in a recent review 27 . PGE 3 has been shown to have less pro-inflammatory and pro-angiogenic effects than PGE 2 .…”
Section: Cox-derived ω-3 Lms In Angiogenesis Inflammation and Cancermentioning
confidence: 99%
“…In a Matrigel-based Boyden chamber assay, PGE 3 inhibited cell invasion in the highly aggressive brain-metastatic melanoma 70W cell line 54 . The cellular receptors of PGE 3 have not been confirmed; some studies have shown that PGE 3 binds to the same receptors as PGE 2 with reduced affinity and potency 27, 55 . Further, a recent study showed that Δ 12 -prostaglandin J 3 (Δ 12 -PGJ 3 ), which is a novel COX-derived metabolite of EPA, potently inhibited progression of leukemia in animal models 56 .…”
Section: Cox-derived ω-3 Lms In Angiogenesis Inflammation and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…DHA and its precursor, eicosapentaenoic acid (EPA) reduce the formation of COX-2-derived PGE 2 (206), a metabolite of omega-6 PUFA-derived AA. COX-2-derived PGE 2 increases VEGF-stimulated invasiveness and angiogenesis through NF-κB (207). There is compelling evidence that EPA could function as a selective COX-2 inhibitor (207209).…”
Section: Pharmacologic Interventions In Ropmentioning
confidence: 99%